PERSEPSI MAHASISWA TERHADAP MANAJEMEN KELAS - Sastika, Nadhiya; Tambunan, Yahya (Graduate Program Magister Manajemen Pendidikan, 2020)
This research found the information about classroom management of lectures on Administration and Supervision of Education in Universitas Negeri Padang. This is a descriptive research. The population was 1055 students and the sample was 148 college students. That was taken by propotional simple random sampling. The instrument of this research was a questionnaire with Likert scale models that had been tested for its validity and reliability. The results of this research showed that classsroom management of lectures on Administration and supervision of education in Universitas Negeri Padang is good enough.